TEACHER’S STRATEGIES ON THE USE OF PROJECT- BASED LEARNING BY CREATING VIDEO IN TEACHING SPEAKING EXPLANATION TEXT DURING COVID-19 - Siti Solihat (Journal of English Education Program (JEEP), 2022)
This study was purposed to find out the teacher’s strategies and investigating students’ perception on the use of Project-Based Learning by creating video in speaking explanation text. This research applied a case study through three data collection techniques, i.e. interview, observation, and questionnaire. The participants of this study consisted of an English teacher and twenty-nine students of the eleventh grade at an Islamic Senior High School in Tasikmalaya. The data from interview and observation were analyzed by using triangulation analysis. Meanwhile, the questionnaire data was calculated by using percentage computation. The findings showed that the teacher used two teaching strategies on the use of Project-Based Learning by creating video in teaching explanation text. They are Situated Learning Strategy and Task Based Learning. Besides, the result of the interview also revealed that the students have positive perceptions on the use of this method. In conclusion, the teacher used two teaching strategies and the students have positive perceptions on Project-Based Learning by creating video. In addition, the further research is recommended to investigate on applying Project- Based Learning by creating video in other English skills (listening, reading, and writing).